Measuring citalopram in blood and central nervous system: revealing a distribution pattern that differs from other antidepressants. (May 2016) - Paulzen, Michael; Lammertz, Sarah E.; Gründer, Gerhard; Veselinovic, Tanja; Hiemke, Christoph; Tauber, Simone C.
Abstract : The aim of this study was to measure blood and cerebrospinal fluid concentrations of citalopram and its weakly active N -demethylated metabolite desmethylcitalopram to account for the distribution between the two compartments. The findings are discussed in the context with own preceding studies on the distribution pattern of different antidepressants. Concentrations of citalopram were measured in blood serum and cerebrospinal fluid of 18 patients treated with daily doses of 10–40 mg. Daily doses were correlated with serum and cerebrospinal fluid concentrations, and serum concentrations were correlated with concentrations in cerebrospinal fluid. Serum concentrations of citalopram and desmethylcitalopram showed no significant correlation to the daily dose, r =0.164, P =0.515, and r =0.174, P =0.505, respectively, whereas citalopram concentrations in serum and cerebrospinal fluid were highly correlated ( r =0.763, P <0.001). The cerebrospinal fluid/serum ratio for citalopram (total=bound+unbound concentration) varied between 0.14 and 0.86 (mean 0.35, SD 0.16). By correcting the mean cerebrospinal fluid/serum ratio for 80% plasma protein binding, cerebrospinal fluid concentrations of citalopram were on average 77% higher than the calculated unbound serum concentration with a ratio of 1.77 (SD 0.81, range 0.68–4.29). Findings indicate a very good ability of citalopram to cross the blood–brain and cerebrospinal fluid barrier. High concentrations of citalopram in the cerebrospinal fluid are indicative of active transport of citalopram into or missing active transport out of the cerebrospinal fluid. The results suggest a high ability of citalopram to enter the brain with sufficiently high drug concentrations at the target sites within the brain, contributing toward clinical efficacy.